Affective Aspect of Junior High School Students Viewed from Self Efficacy - U H Putri; Mardiyana Mardiyana; D R S Saputro (Universitas Sebelas Maret, 2017)
The relevance of this research is the growth of character values for students in Indonesia. Mathematics is a subject that builds character value for students. This can be seen from how students view mathematics from their perspective. Students' perspective can be seen as a student's assessment of the mathematics such as from the attitudes, interests, self-concepts, values, and morals shown in the learning process of mathematics with the students' willingness to act positively or negatively. In mathematics learning, this is called the affective aspect (AA). One of the factors influencing students’ AA is self-efficacy (SE). SE is a belief that is someone has to complete a given task or problem. There are three categories of SE that owned by students, that is high, medium, and low. The purpose of this study is to determine which ones provide better mathematics AA than students. The research subjects are 294 students in Karanganyar Regency. Data is obtained by questionnaire. Based on the results of data analysis, the conclusion is students with high SE have better mathematics AA than students with moderate and low SE, while students with moderate SE have better mathematics AA than students with low SE.